Adsorption Study of Methylene Blue and Methyl Orange Using Green Shell (Perna Viridis) - Febi Indah Fajarwati; Nadya Ika Yandini; Mai Anugrahwati; Amri Setyawati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Green shell is generally disposed of and become environmental contaminants. In this study, the green shell was used as material to adsorb dyes residue: methylene blue and methyl oranges. Green shell waste from seafood was prepared by removing the dirt then dried at room temperature. It was followed by roughly crushing before being placed in the furnace at temperatures of 300, 500, 700 and 900 °C. The selected adsorbents were sieved at 200 mesh. The adsorbents were characterized by FTIR and SEM-EDX to evaluate their functional groups and morphology. Furthermore, the adsorption process was evaluated by determining the kinetic adsorption models. The results of the FTIR characterization showed the vibration of Ca(OH)2 bone at a wave number of 3400 cm-1 and morphological analysis by SEM showed a homogeneous surface. Adsorption kinetics results obtained from the variation of time with the initial adsorbate concentration showed the kinetic model of both methylene blue and methyl orange adsorption onto the adsorbent followed a pseudo-second order.